Development agencies, grant system, and financial support for SMEs in Turkey - Dinçer, Hasan; Hacıoğlu, Ümit; Özkul, Abdullah Önder (IGI Global, 2014)
SMEs form 90% of commercial businesses in Turkey and the support given to SMEs means support directly given to the real sector in a vast scale. SMEs have some problems currently that are accepted as structural throughout Turkey, such as that they were constituted in form of family companies, that they do not use financial instruments sufficiently, that they do not work with professional executives, their commercial activities without invoice, etc. There could be other common problems that SMEs can meet with as related to sector or location. The main duties of Development Agencies is to mobilize commercial potential in region, to support sectors that have the potential to grow, and thus, to decrease the difference of development between regions. This chapter explores SMEs in Turkey.
Keywords: Development Agencies; Grant System; Financial Support; SMEs; Turkey